Pengaruh Variabel Makro Ekonomi Terhadap Jakarta Islamic Index (JII) Periode 2018-2022 - Yusril Arfan Sanaky; Anggriyani Safitri Safitri; Nur Aisyah Indarningsih (Prodi Ekonomi Syariah IAIN Sorong, 2023)
This study was designed to determine the effect of macroeconomic variables such as interest rates, exchange rates, and inflation (as well as the COVID-19 pandemic) on the Jakarta Islamic Index (JII) for the period January 2018–December 2022. The method used is quantitative with the error correction model (ECM) analysis technique. The test results provide a relationship that the IDR / USD Exchange Rate has a significant positive effect on JII in the long and short term, the BI Rate has a significant positive effect in the long term. The BI rate does not affect JII in the short term, as does inflation, which also has no short- or long-term effect. Meanwhile, the pandemic has a significant negative relationship to JII both in the long and short term. Based on the ECM method used in this study, it shows that the methodology is good for analysis because of the amount of ECT received.